CORRELATION BETWEEN TBARS VALUE IN SERUM AND TISSUE AS OXIDATIVE STRESS MARKERS IN PREMALIGNANT AND MALIGNANT CERVICAL LESIONS - Asotić, Amir; Asotić Memić , Anida; Memić, Muhamed; Asotić, Kerim; Asotić, Amra (Sanamed, 2024)
Introduction: Numerous risk factors affect the development of cervical intraepithelial neoplasia (CIN) and cervical cancer (CC), with high-risk subtypes of the human papillomavirus (HPV) being the most significant. Oxidative stress (OS) plays an important role in the pathogenesis of CC and CIN as a risk factor. A commonly used marker of OS, which measures lipid peroxidation products in cells, tissues, and body fluids, is thiobarbituric acid reactive substances (TBARS). This study aimed to determine the correlation between TBARS levels in tissue and serum and evaluate their diagnostic significance in patients with cervical lesions. Patients and methods: The research was conducted at the Clinical Center of the University of Sarajevo. The experimental group consisted of 200 female patients with biopsy-confirmed changes consistent with CIN, carcinoma in situ (CIS), and CC. The control group (N=40) had biopsy-confirmed non-pathological findings. The concentration of TBARS was determined for all subjects from biopsy samples and serum according to standard laboratory practice. Results: We found a significant difference in serum/tissue TBARS levels between study groups. Serum/tissue levels of TBARS in patients with CIS were significantly higher compared to the control group, patients with CIN 1, CIN 2, CIN 3, and patients with CC (p<0.05 for all). There was a significant positive correlation between TBARS levels in serum (µM) and TBARS levels in tissue (µM) (Pearson’s r=0.494, p<0.001). Tissue and serum TBARS levels are major differentiation markers between CIS patients and the control group, as well as patients with CIN 1, CIN 2, CIN 3, and CC. Conclusion: Patients with CIN and CC exhibit increased oxidative stress, indicated by higher levels of TBARS in their tissue and serum compared to healthy controls. TBARS levels in tissue are positively correlated with levels in serum. Tissue and serum TBARS levels are significant markers for differentiating the clinical stages of the disease.